Quality and Storability of Mango During Zero Energy Cool Chamber (ZECC) - Andi Dirpan; Muhammad Tahir Sapsal; Adiansyah Syarifuddin; Mulyati M Tahir; Kamilia Nur Yaumil Ali; Abdul Kadir Muhammad (International Journal of Agriculture System, 2018)
Many researchhavefound thatthe use of zero energy coolchamber (ZECC) extend the shelf life of stored fruits and vegetables. There is a lack of study conducted in Indonesia about the use of ZECC to keep mangos after harvesting though. The present study, therefore, was aimed to understand the quality and storability of stored mangos in ZECC. Three different storage containers, a ZECC, ambient, and refrigerator with different average RH and temperature, were used to place selected ripe mangos (Mangifera indica L) that were manually harvested from farmers’ field nearby. The ZECC was set up at the residential complex for lecturer of Hasanuddin University as the experiment site. Results showed that mangos inside ZECC were acceptable until eleven days of storage after considering both quality and sensory evaluation. The result suggests that ZECC can maintain mango’s quality and extend its shelf life, which reveals that ZECC seems promisingfor commercial application